2019
DOI: 10.1029/2018jd028620
|View full text |Cite
|
Sign up to set email alerts
|

Using Saha‐Boltzmann Plot to Diagnose Lightning Return Stroke Channel Temperature

Abstract: Based on the high time‐resolved spectra of a cloud‐to‐ground lightning flash with seven return strokes captured by a high‐speed slitless spectrograph, this work was the first to use the Saha‐Boltzmann plot method for the determination of the lightning return stroke channel temperature. The channel temperatures of the seven return strokes ranged from 21370 to 26500 K. Compared with the traditional Boltzmann plot method, the Saha‐Boltzmann plot method can provide more reliable temperature estimation for lightnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Previously, it was shown that the total spectral intensity of the ionization lines of nitrogen and oxygen in the visible and near infrared (400-1,000 nm) during the return stroke of natural lightning was well correlated with the change in amplitude of the electric field (Wang et al, 2016). In a later study, it was shown that the temperature of the return stroke channel can be calculated from the spectral emission intensities of the ionization lines of NI and NII in the visible to the near infrared range (444-868 nm) using a form of the Saha-Bolzmann method (Liu et al, 2019). Thus, it seems reasonable that the optical intensity of the generated spark can also be correlated with its electric field and therefore LFI is equivalent to its current as previously demonstrated by Wang et al (1998).…”
Section: Methodsmentioning
confidence: 92%
“…Previously, it was shown that the total spectral intensity of the ionization lines of nitrogen and oxygen in the visible and near infrared (400-1,000 nm) during the return stroke of natural lightning was well correlated with the change in amplitude of the electric field (Wang et al, 2016). In a later study, it was shown that the temperature of the return stroke channel can be calculated from the spectral emission intensities of the ionization lines of NI and NII in the visible to the near infrared range (444-868 nm) using a form of the Saha-Bolzmann method (Liu et al, 2019). Thus, it seems reasonable that the optical intensity of the generated spark can also be correlated with its electric field and therefore LFI is equivalent to its current as previously demonstrated by Wang et al (1998).…”
Section: Methodsmentioning
confidence: 92%
“…We use the LFI (integrated optical emission spectra) of the generated spark, which in essence is due to the ionization of the gases in the path of the spark. In natural lightning it was shown that the emission spectra are well correlated with the temperature of the return stroke 24 and the electric field 25 . Thus, it seems reasonable that the optical intensity of the generated spark can also be correlated with its electric field and therefore LFI is equivalent to its current as previously demonstrated by Wang et al .…”
Section: Experimental Design and Measurementsmentioning
confidence: 99%
“…Uman and Orville (1965) as well as Griem (1964) have reported that the channel satisfies the LTE condition. Under the LTE condition, the Boltzmann Plot method can be used to calculate the channel temperature (Liu et al., 2019). ln(IλgA)=1kTE+c where c is a constant, and I is the intensity of the spectral line, and G, A and E are the statistical weights, transition probability and excitation energy, respectively.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Uman and Orville (1965) as well as Griem (1964) have reported that the channel satisfies the LTE condition. Under the LTE condition, the Boltzmann Plot method can be used to calculate the channel temperature (Liu et al, 2019).…”
Section: Temperature Calculationmentioning
confidence: 99%